Haemodynamic, renal sodium handling, and neurohormonal effects of acute administration of low dose losartan, an angiotensin II receptor antagonist, in preascitic cirrhosis. Issue 1 (1st January 2000) - Girgrah, N; Liu, P; Collier, J; Blendis, L; Wong, F
Abstract : BACKGROUND: The renin-angiotensin system may be implicated in the subtle sodium handling abnormality in preascitic cirrhosis. AIMS: To assess the role of angiotensin II in sodium homoeostasis in preascitic cirrhosis, using losartan, its receptor antagonist. PATIENTS: Nine male, preascitic cirrhotic patients, and six age matched, healthy male controls. METHODS: A dose response study using 2.5, 5, 7.5, and 10 mg of losartan was performed on a daily 200 mmol sodium intake, followed by repeat studies with the optimal dose, 7.5 mg of losartan, to determine its effects on systemic and renal haemodynamics, renal sodium handling, and neurohumoral factors. RESULTS: Preascitic cirrhotic patients had significantly reduced baseline urinary sodium excretion compared with controls (154 (8) versus 191 (12) mmol/day, p<0.05), associated with significantly reduced systemic angiotensin II levels (6.0 (1.7) versus 39.5 (10.0) pmol/l, p=0.002). Losartan 7.5 mg normalised renal sodium handling in the preascitic cirrhotic patients (202 (12) mmol/day, p=0.05 versus baseline), without any change in systemic or renal haemodynamics, but with significantly increased systemic angiotensin II levels (7.8 (2.3) pmol/l, p=0.05 versus baseline). Losartan had no effect on renal sodium handling in controls. CONCLUSIONS: In preascitic cirrhotic patients, the subtle renal sodium retention, paradoxically associated with low systemic neurohumoral factor levels, is improved with low dose losartan, suggesting the involvement of angiotensin II via its direct action on the renal tubule.